1990
DOI: 10.1111/j.1365-2826.1990.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localization of Angiotensinogen and Angiotensin II in the Rat Pituitary

Abstract: The presence and distribution of angiotensinogen and angiotensin II (All) were demonstrated in rat pituitary by immunocytochemical staining with the avidin-biotin-peroxidase method, using primary polyclonal antibodies specific for angiotensinogen and All. Silver enhancement of the reaction product was used to intensify lightly stained areas. Attempts were made to identify immunopositive cells by colocalization studies with antisera against luteinizing hormone, prolactin and S-100, a glial cell protein. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Deschepper and Ganong (1991) and Ganong et al (1989) reported that AGT is located in a separate population of cells and does not co-localize with any known anterior pituitary hormone. By contrast, Sernia et al (1992Sernia et al ( ,1997 and Thomas and Sernia (1990) detected AGT in gonadotropes and also in a population of perisinusoidal cells. In the rat pituitary, RAS components, either AGT (Ganong et al 1989; Thomas and Sernia 1990;Deschepper and Ga-nong 1991;Sernia et al 1992) or renin (Naruse et al 1981(Naruse et al ,1986, were not detected in lactotropes.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Deschepper and Ganong (1991) and Ganong et al (1989) reported that AGT is located in a separate population of cells and does not co-localize with any known anterior pituitary hormone. By contrast, Sernia et al (1992Sernia et al ( ,1997 and Thomas and Sernia (1990) detected AGT in gonadotropes and also in a population of perisinusoidal cells. In the rat pituitary, RAS components, either AGT (Ganong et al 1989; Thomas and Sernia 1990;Deschepper and Ga-nong 1991;Sernia et al 1992) or renin (Naruse et al 1981(Naruse et al ,1986, were not detected in lactotropes.…”
mentioning
confidence: 72%
“…By contrast, Sernia et al (1992Sernia et al ( ,1997 and Thomas and Sernia (1990) detected AGT in gonadotropes and also in a population of perisinusoidal cells. In the rat pituitary, RAS components, either AGT (Ganong et al 1989; Thomas and Sernia 1990;Deschepper and Ga-nong 1991;Sernia et al 1992) or renin (Naruse et al 1981(Naruse et al ,1986, were not detected in lactotropes. The presence of AII in lactotropes has been reported by some authors (Steele et al 1982).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In the anterior pituitary, Ang II is produced locally in gonadotrophs and acts in a paracrine manner on lactotrophs to stimulate prolactin release (Aguilera et al, 1982;Paglin et al, 1984;Ganong et al, 1989;Thomas and Sernia, 1990), an effect mediated by AT 1 receptors (Becú-Villalobos et al, 1994;Moreau et al, 1994). Estrogen treatment of OVX rats downregulates the number of AT 1 receptors in the anterior pituitary (Chen and Printz, 1983;Carriére et al, 1986;Seltzer et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In the anterior pituitary, Ang II is synthesized locally and stimulates prolactin release (Steele et al, 1981;Aguilera et al, 1982;Schramme and Denef, 1983;Ganong et al, 1989;Jones et al, 1990;Steele and Myers, 1990;Thomas and Sernia, 1990). Ang II also participates in brain mechanisms controlling pituitary prolactin release, but here its role is inhibitory rather than stimulatory Steele, 1989, 1991).…”
Section: Abstract: Angiotensin II Receptors; Catecholamines; Tyrosinmentioning
confidence: 99%